Superoxide dismutase from the psychrophilic Antarctic eubacterium Pseudoalteromonas haloplanktis - CASTELLANO, IMMACOLATA; RUOCCO, MARIA ROSARIA; DE VENDITTIS, EMMANUELE; MASULLO M; DI MARO A; CHAMBERY A (2005)
The antioxidant function of Fe- and Mn-containing superoxide dismutases (SOD) observed under constraints from extreme rather than mild cellular conditions could reflect an adaptive evolution to oxygen tolerance in the structural organisation of this class of enzymes. For instance, the mitochondrial human Mn-SOD and the hyperthermophilic archaeal Fe-SOD from Sulfolobus solfataricus (SsSOD) share a similar structural organisation. Further studies on members of this ubiquitous enzyme isolated from differently adapted micro–organisms could give useful information on possible adaptive mechanisms in the structure-function relationships of this SOD family. For this reason, this enzyme has been purified and characterised from Pseudoalteromonas haloplanktis, a psychrophilic eubacterium isolated from marine Antarctic sediments. Two chromatographic steps on DEAE-Sepharose and HTP allowed to purify SOD from P. haloplanktis (PhSOD) to homogeneity. The relative molecular weight of the purified enzyme estimated by SDS-PAGE is about 20,000. As SsSOD, also PhSOD shows a homotetrameric structure, as determined by gel filtration. PhSOD has an unusual thermal stability for a psycrophilic enzyme, as evaluated by its half-life of 10 min at 52°C. Similar results were obtained by UV-melting curves. Enzymatic assays showed that PhSOD has a specific activity of 6500 U/mg. The enzyme is inactivated by hydrogen peroxide and it is inhibited by sodium azide, whereas PMSF, a specific inactivator of the archaeal SsSOD, has no effect. Future research plan includes the determination of the metal content and the cloning of the gene encoding PhSOD. To this aim, a molecular probe has been designed on the basis of the amino acid sequence of some fragments of the purified protein.